ENFORCEMENT OF LAWS AGAINST BROADCASTING RIGHTS PIRACY FROM A HOLISTIC PERSPECTIVE IN THE CONTEXT OF LEGAL CERTAINTY - Handiriono, Raden; Dharliana Hardjowikarto; Adhinda Maharani; Nursyifah Zakiah (Cirebon International Conference on Education and Economics Proceeding, 2024)
The rapid acceleration of broadcasting rights distribution in Indonesia has introduced new challenges and threats to the enforcement of broadcasting rights and copyright laws. This phenomenon manifests holistically across various forms and media, including the piracy of broadcasting rights via social media platforms, where broadcast content is shared illegally without the consent of the rights holders, as well as the unauthorized use of broadcasting rights for commercial and non-commercial purposes, such as broadcasts played in cafes and bars without paying royalties. This study aims to explore the enforcement of laws against broadcasting rights piracy in Indonesia within the context of legal certainty. Additionally, it examines the efficiency of institutions like the Indonesian Broadcasting Commission (KPI) and the Ministry of Communication and Informatics (Kominfo) in enforcing broadcasting rights without royalties that are distributed illegally, both through social media and live broadcasts. The research employs a qualitative and normative juridical approach by reviewing and understanding the regulations related to broadcasting rights and copyright. Copyright falls under the scope of intellectual property rights and is governed by Law Number 28 of 2014 on Copyright and Law Number 32 of 2002 on Broadcasting. Data is obtained through literature studies and the analysis of these regulations. It is hoped that with appropriate solutions, the enforcement of broadcasting rights laws can become more effective and efficient, providing the necessary legal certainty to protect the rights of broadcasting rights holders in Indonesia. The increasing incidence of live broadcast piracy on the internet has shifted public habits from watching on official platforms to viewing on illegal sites. This undoubtedly harms the rights holders due to the services of these illegal sites.